A decade in review: bibliometric analysis of sustainable performance trends in higher education institutes - Umar, Shahawati Binti; Ahmad, Jawaria; Bukhori, Muhammad Anas Bin Mohd; Mohd Ali, Khairul Anuar; Wan Hussain, Wan Mohd Hirwani (Frontiers in Education, 2024)
The sustainable performance of higher education institutes (HEIs) is key to efficiently manage educational institutes in the long run, to get financial aid from the government, and to keep the interest of stakeholders in the institutions. Researchers have focused on examining the impact of a sustainable curriculum, sustainable teaching methodologies, sustainable campuses, and tools for assessing sustainability in HEIs in past literature. The present bibliometric analysis, combined with network analysis, aims to explore the literature to identify research gaps in the field of sustainable performance or sustainability performance of HEIs. We have employed a Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) flow diagram to analyze the results obtained from Scopus, Web of Science (WoS), and EBSCOhost databases. A bibliometric analysis using Biblioshiny web application and VOSviewer software was performed on the 263 articles included in the study after screening. The results revealed that the annual growth rate of publications is increasing, indicating that the sustainability performance of HEIs is gaining momentum after the introduction of the Sustainable Development Goals (SDGs) in 2017. The production of articles in the field is highest from advanced European countries and the United States, but only a few articles are published from Asian countries. The authors with the highest number of publications and the most cited research article in the field are Leal Filho and Wals, respectively. Authors keywords in HEIs (or institutions) not only have a strong link with sustainability, sustainable education, green campus, and sustainability assessment but also have a small network with sustainable performance, green knowledge sharing, green knowledge management, green human resource management practices, green teams, change management, and organizational commitment. These findings can be used by future researchers to identify unexplored research areas in different contexts.